Secular models and Kozai resonance for planets in coorbital non-coplanar motion - Giuppone, Cristian Andrés (2016)
In this work, we construct and test an analytical model and a semi-analytical secular model for two planets locked in a coorbital non-coplanar motion, comparing the results with the restricted three-body problem. The analytical average model replicates the numerical N-body integrations, even for moderate eccentricities (≲0.3) and inclinations (≲10°), except for the regions corresponding to quasi-satellite and Lidov-Kozai configurations. Furthermore, this model is also useful in the restricted three-body problem, assuming a very low mass ratio between the planets. We also describe a four-degree-of-freedom semi-analytical model valid for any type of coorbital configuration in a wide range of eccentricities and inclinations. Using an N-body integrator, we have found that the phase space of the general three-body problem is different to the restricted case for an inclined system, and we establish the location of the Lidov-Kozai equilibrium configurations depending on the mass ratio. We study the stability of periodic orbits in the inclined systems, and find that apart from the robust configurations, L4, AL4 and QS, it is possible to HARBOUR two Earth-like planets in orbits previously identified as unstable (U) and also in Euler L3 configurations, with bounded chaos.